2019
DOI: 10.1515/ntrev-2019-0045
|View full text |Cite
|
Sign up to set email alerts
|

Materials characterization of advanced fillers for composites engineering applications

Abstract: Four different minerals were investigated; hollow spheres of calcium carbonate, platy mica, needle like wollastonite and glassy perlite and characterized via iGC for surface energy, Freeman powder rheology for flow characterization, cyclic uniaxial die compaction for modulus of elasticity and frequency dependent sound absorption properties. Particle surface energy and particle shape strongly affected the packing density of powder beds. In the case of higher porosity and thus lower bulk density, the powders aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The ETM fillers also displayed high aspect ratios which generally translate to high reinforcing potential. Platy fillers provide reinforcement along both dimensions of its plate compared to fibers which reinforce only along its axial dimension [12]. Thus, platy fillers offer greater reinforcing potential than fibers of equivalent aspect ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The ETM fillers also displayed high aspect ratios which generally translate to high reinforcing potential. Platy fillers provide reinforcement along both dimensions of its plate compared to fibers which reinforce only along its axial dimension [12]. Thus, platy fillers offer greater reinforcing potential than fibers of equivalent aspect ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, nanomaterials mixed with other metals can improve contrast performance and have favored attentions interest recently [50]. Luminomagnetic nanoparticles that possessed core/shell structures (and Fe 3 O 4 NPs coated with luminescent material) show some advantages [51]. Although optical imaging and magnetic imaging can be achieved because of the existence of rare earth up-conversion fluorescent nanoparticles, the imaging effect is not ideal, especially magnetic imaging [52].…”
Section: T 2 Sign Imaging Of Fe 3 O 4 Nanomaterialsmentioning
confidence: 99%
“…None of the preceding studies, based on a literature survey, has discussed the effects of CEO on the flammability and thermal stability as well as morphology of biopolymer composites of SPN reinforced with SPS. It is well known in composites that the use of nanofillers such as nanocelluloses is important in influencing the composite properties such as thermal performances [70]. Lapčík et al [70] reported that nanofillers are commonly used for structural and non-structural components, and packaging as well as advanced coating applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known in composites that the use of nanofillers such as nanocelluloses is important in influencing the composite properties such as thermal performances [70]. Lapčík et al [70] reported that nanofillers are commonly used for structural and non-structural components, and packaging as well as advanced coating applications. Therefore, this study aimed to investigate the possible effects of using EO as fillers on the flammability, thermal stability and morphological properties of SPN/SPS biopolymer composites at different loadings.…”
Section: Introductionmentioning
confidence: 99%